Design a typical lock-in amplifier based on Arduino and MATLAB - Lu, Kun (Highlights in Science, Engineering and Technology, 2024)
The collection of low-frequency signals is very common in the use of sensors. However, 1/f noise and other low-frequency noise will drastically impact the quality of the low-frequency signal, which is why lock-in amplification is widely used to handle the original signal and improve the signal-to-noise ratio. So this research collected the original signal through Arduino and added 1/f noise to form the real data researchers usually got in reality, then MATLAB was used to perform the steps like modulating the mixed signal and demodulating it to get the final signal. Compared with the original data, the demodulated signal was similar, the causes of the differences between the two of them are likely because of the collecting part, the original signal is not a square wave in the true sense, and the changes from low to top resulted in the deviation. Generally speaking, lock-in amplification perfectly separates low-frequency signals from 1/f noise, which can help researchers better process signals and improve the sensors.